Presence of nanotechnology in agriculture: bibliometric approach - Karmen Stopar (Acta Agriculturae Slovenica, 2016)
Increasing number of scientific publications points to quick developments in the field of nanoscience and nanotechnology. Nanotechnology offers potentials of unimaginable proportions. Innovative possibilities present themselves in many areas of human activity, including agriculture, for example in precision farming, reduction of pollution and increasing crop yields. We bibliometrically assessed interactions between nanotechnology and agriculture. With co-word analysis in particular, we examined aspects of agro-nano applications related to plant protection. In order to analyze and map the structure of knowledge, we employed selected terms from a general citation database Web of Science (WOS) as well as specialized bibliographic database CAB Abstracts which covers life sciences with a special emphasis on agriculture. Our thematic maps (visualization) present some principal themes and relations among them. Pesticides, biosensors and detection are the main keywords in the network of words from article titles and network of the KeyWords+. Analysis of controlled terms (descriptors, classification codes) from CAB Abstracts in connection with pesticides shows two important directions of research: pollution and environmental topics, and topics related to human health, experimental animals and related.